Protandim does not influence alveolar epithelial permeability or intrapulmonary oxidative stress in human subjects with alcohol use disorders - Burnham, Ellen L; McCord, Joe M; Bose, Swapan; Brown, Lou Ann S; House, Robert; Moss, Marc; Gaydos, Jeanette (American journal of physiology. Lung cellular and molecular physiology, 2012)
Alcohol use disorders (AUDs), including alcohol abuse and dependence, have been linked to the development of acute lung injury (ALI). Prior clinical investigations suggested an association between AUDs and abnormal alveolar epithelial permeability mediated through pulmonary oxidative stress that may partially explain this relationship. We sought to determine if correcting pulmonary oxidative stress in the setting of AUDs would normalize alveolar epithelial permeability in a double-blinded, randomized, placebo-controlled trial of Protandim, a nutraceutical reported to enhance antioxidant activity. We randomized 30 otherwise healthy AUD subjects to receive directly observed inpatient oral therapy with either Protandim (1,350 mg/day) or placebo. Subjects underwent bronchoalveolar lavage (BAL) and blood sampling before study drug administration and after 7 days of therapy; all AUD subjects completed the study protocol without adverse events. BAL total protein was measured at each timepoint as an indicator of alveolar epithelial permeability. In subjects with AUDs, before study drug initiation, BAL total protein values were not significantly higher than in 11 concurrently enrolled controls (P = 0.07). Over the 7-day study period, AUD subjects did not exhibit a significant change in BAL total protein, regardless of their randomization to Protandim {n = 14, -2% [intraquartile range (IQR), -56-146%]} or to placebo [n = 16, 77% (IQR -20-290%); P = 0.19]. Additionally, among those with AUDs, no significant changes in BAL oxidative stress indexes, epithelial growth factor, fibroblast growth factor, interleukin-1β, or interleukin-10 were observed regardless of drug type received. Plasma thiobarbituric acid reactive substances, a marker of lipid peroxidation, decreased significantly over time among AUD subjects randomized to placebo (P < 0.01). These results suggest that Protandim for 7 days in individuals with AUDs who are newly abstinent does not alter alveolar epithelial permeability. However, our work demonstrates the feasibility of safely conducting clinical trials that include serial bronchoscopies in a vulnerable population at risk for acute lung injury.